Games, design and play : a detailed approach to iterative game design - Macklin, Colleen, ....-; Sharp, John, 1967- (Boston (Mass.) : Addison-Wesley, 2016)
The play-focused, step-by-step guide to creating great game designs This book offers a play-focused, process-oriented approach for designing games people will love to play. Drawing on a combined 35 years of design and teaching experience, Colleen Macklin and John Sharp link the concepts and elements of play to the practical tasks of game design. Using full-color examples, they reveal how real game designers think and work, and illuminate the amazing expressive potential of great game design. Focusing on practical details, this book guides you from idea to prototype to playtest and fully realized design. You'll walk through conceiving and creating a game's inner workings, including its core actions, themes, and especially its play experience. Step by step, you'll assemble every component of your videogame, creating practically every kind of play: from cooperative to competitive, from chance-based to role-playing, and everything in between. Macklin and Sharp believe that games are for everyone, and game design is an exciting art form with a nearly unlimited array of styles, forms, and messages. Cutting across traditional platform and genre boundaries, they help you find inspiration wherever it exists. Games, Design and Play is for all game design students, and for beginning-to-intermediate-level game professionals, especially independent game designers. Bridging the gaps between imagination and production, it will help you craft outstanding designs for incredible play experiences!
Keywords: Video games -- Design